A biodegradable Zn-Mg-Ca-Sr zinc alloy and its preparation method and application
By adding calcium and strontium to the zinc alloy, the Zn-Mg-Ca-Sr zinc alloy is formed, which solves the problem of low strength of zinc alloy and achieves significant improvement in the strength, hardness and toughness of the alloy. It is suitable for the application of biodegradable implants.
Patent Information
- Application Number
- CN202211436599.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-11-16
AI Technical Summary
The existing zinc alloy has low strength and insufficient comprehensive performance, making it difficult to meet the strength requirements of biodegradable implants for healing and rehabilitation in the human body.
Through alloying technology, calcium (Ca) and strontium (Sr) elements are added to form Zn-Mg-Ca-Sr zinc alloy. The specific Ca/Sr ratio and preparation method are used to form an η-Zn dendrite matrix and Mg2Zn11, CaZn13 and (Cax, Sr1-x) Zn13 reinforced phases to improve the strength and toughness of the alloy.
It significantly improves the strength, hardness and toughness of zinc alloys, improves its corrosion performance in the biological environment, and meets the needs of biodegradable implants to heal and recover in the human body.
Smart Images

Figure CN116219227B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multi-element biodegradable Zn-Mg-Ca-Sr zinc alloys, and specifically relates to a biodegradable Zn-Mg-Ca-Sr zinc alloy and a preparation method and application thereof. Background Art
[0002] In recent years, with the advancement of medical technology, implants have played an indispensable role in the treatment of many diseases, such as various fractures, tissue and organ stenosis, minimally invasive support and fixation devices for the digestive tract, various blood clots and other damaged parts. After the function of the defect or repaired part is restored, the plant body needs to be removed from the body. Traditional metal materials such as stainless steel, titanium alloy, and cobalt-based alloy are used as implants, and there is a problem of requiring a second operation to remove them, which not only increases the cost of the operation, but also brings pain and risk of the second operation to the patient. In addition, these traditional metals may also release harmful metal ions, stress shielding and other adverse effects during their service, which directly affect the regeneration and functional reconstruction of surrounding tissues, have an extremely adverse effect on patients, and even lead to serious sequelae.
[0003] The emergence of biodegradable and absorbable implants has effectively improved such problems. Biodegradable implants serve as necessary supports to assist the healing, cell regeneration and reconstruction of diseased lesions during service, and then gradually degrade. Biodegradable polymers were first studied in depth as candidate materials for biodegradable implants (such as PLA), but it was soon discovered that although biodegradable polymers have good biocompatibility and predictable degradation products, they are insufficient in strength and may cause a series of problems such as inflammation, thrombosis, and delayed healing, and can only be applied to soft tissue organs. As hard tissue implants for tissue and organ repair and implants with high strength requirements, the mechanical properties of metal materials are significantly better than polymers, and people have turned their attention to degradable metal materials. In the past two decades, biodegradable alloys have been widely studied in clinical applications, especially bone nails, bone plates, cardiovascular stents, gastrointestinal organ stenosis, minimally invasive surgical wound closure clips, staplers, etc., to meet the clinical requirements of implants for healing and rehabilitation of these parts of the human body. Magnesium (Mg) and iron (Fe) and their alloys have been widely studied as candidate materials for degradable medical applications. Although magnesium-based materials have excellent biocompatibility and low thrombogenicity, they corrode quickly in physiological environments, causing the mechanical integrity and functionality of implants to fail in the early stages of bone healing (for example, the usual organ complete repair and reconstruction cycle takes 6-12 months, while magnesium alloy devices usually degrade severely in 3-6 weeks). At the same time, the rapid corrosion of magnesium alloys will produce a large amount of hydrogen, which is released around the implant or in the skin tissue layer to form bubbles, causing serious cell tissue inflammation, emphysema damage, nerve pain and other sequelae. At present, the mechanical properties and rapid corrosion problems of magnesium-based materials can be improved through alloying, thermomechanical processing and surface modification technologies, but magnesium-based materials are still far from reaching the healing cycle of degradable metal materials implanted in the human body. Compared with magnesium-based materials, iron-based materials have excellent mechanical properties, but the degradation rate in the physiological environment is too slow, resulting in the implant not being completely degraded after achieving its service purpose.
[0004] As one of the essential elements for the human body, zinc has become a research hotspot in the field of biodegradable materials because of its corrosion rate between magnesium and iron, as well as good biocompatibility, absorbability and degradability. Due to the poor mechanical properties of pure zinc, it cannot meet the mechanical property requirements of implant materials. Alloying has been widely studied as an indispensable method to improve its mechanical properties. People have designed and developed many new zinc alloys, among which magnesium has been widely used in zinc alloying due to its good biocompatibility and strengthening effect. Such as Zn-Mg, Zn-Ca, Zn-Sr, Zn-Mg-Ca, Zn-Mg-Ca, Zn-Ca-Sr and Zn-Mg-Mn.
[0005] Calcium and strontium are the main components of bones and are also necessary elements for cell chemical signal transduction. They participate in mineralization and enzyme reactions in the human body. For example, strontium can improve bone metabolism, improve the impact toughness of bones, detoxify and repair cells, and achieve a certain effect in preventing cardiovascular and cerebrovascular diseases. It is known as the "longevity" element. 99% of the calcium in the body is in the bones, and 1% is distributed in the body fluids. It maintains normal nerve excitability and electrophysiological activity of the heart, and is an important element for physiological activities and nerve transmission. In addition, excess calcium and strontium metabolites can be transported out of the human body through the circulatory system. More importantly, calcium and strontium, as alloying elements, can also improve the strength and corrosion rate of the alloy when added to the alloy. Therefore, pure zinc is usually alloyed with various nutrients to obtain suitable mechanical properties and corrosion rates. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a biodegradable Zn-Mg-Ca-Sr zinc alloy and a preparation method and application thereof to solve the technical problems of low strength and insufficient comprehensive performance of zinc alloys in view of the deficiencies in the above-mentioned prior art.
[0007] The present invention adopts the following technical solutions:
[0008] A biodegradable Zn-Mg-Ca-Sr zinc alloy comprises the following elements by weight percentage: Mg 1.10% to 1.20%, the total amount of Ca and Sr is less than or equal to 0.3%, the balance is Zn, the mass percentage ratio of Ca to Sr is 0, 0.5, 1, 1.5 or 2, the matrix structure of the biodegradable Zn-Mg-Ca-Sr zinc alloy is η-Zn dendrite, and the strengthening phases are eutectic rod-shaped Mg2Zn distributed between the dendrites. 11 Phase, intragranular and grain boundary bulk CaZn 13 Phase and (Ca x , Sr. 1-x )Zn 13 Solid solution.
[0009] Specifically, when the mass percentage ratio of Ca to Sr is 0, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 9.36%; when the mass percentage ratio of Ca to Sr is 0.5, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 24.33%, CaZn 13 The volume fraction of the phase is 5.01%; when the mass percentage ratio of Ca and Sr is 1, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 26.24%, CaZn 13 The volume fraction of the phase is 3.53%; when the mass percentage ratio of Ca to Sr is 1.5, the eutectic rod-shaped Mg2Zn 11The volume fraction of the phase is 23.56%, CaZn 13 The volume fraction of the phase is 4.73%; when the mass percentage ratio of Ca to Sr is 2, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 29.07%, irregular blocky CaZn 13 The volume fraction of the phase is 2.89%.
[0010] Specifically, when the mass percentage ratio of Ca and Sr is 0, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 44.32 μm; when the mass percentage ratio of Ca and Sr is 0.5, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 37.02 μm; when the mass percentage ratio of Ca and Sr is 1, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 36.11 μm; when the mass percentage ratio of Ca and Sr is 1.5, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 19.73 μm; when the mass percentage ratio of Ca and Sr is 2, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 23.39 μm.
[0011] Specifically, when the mass percentage ratio of Ca and Sr is 0, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 76.51 HBW; when the mass percentage ratio of Ca and Sr is 0.5, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 91.08 HBW; when the mass percentage ratio of Ca and Sr is 1, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 84.95 HBW; when the mass percentage ratio of Ca and Sr is 1.5, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 94.91 HBW; when the mass percentage ratio of Ca and Sr is 2, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 89.96 HBW.
[0012] Another technical solution of the present invention is a method for preparing a biodegradable Zn-Mg-Ca-Sr zinc alloy, comprising the following steps:
[0013] In an inert atmosphere, zinc and magnesium are heated in sequence until they are completely melted to obtain a melt, and then calcium and / or strontium particles are added to the melt, the temperature is increased and the melt is fully stirred, and the melt is kept warm to obtain a Zn-Mg-Ca-Sr zinc alloy melt;
[0014] The Zn-Mg-Ca-Sr zinc alloy melt is allowed to stand, refined and slag removed, and then poured and demolded to obtain the biodegradable Zn-Mg-Ca-Sr zinc alloy.
[0015] Specifically, the zinc and magnesium are heated until they are completely melted to obtain a melt as follows:
[0016] The flow rate of the inert gas is controlled to be 15-20 L / min, and the melting temperature is controlled to be 550-600° C. to heat zinc and magnesium, and the temperature is kept for 30-40 minutes to obtain a zinc-magnesium melt.
[0017] Specifically, the preparation of the Zn-Mg-Ca-Sr zinc alloy melt is as follows:
[0018] The stirring speed is controlled to be 50-80 rpm, the mixture is stirred at 550-600° C. for 20-30 minutes, and then kept warm for 12-15 minutes to obtain a Zn-Mg-Ca-Sr zinc alloy melt.
[0019] Specifically, the standing time is 3 to 5 minutes.
[0020] Specifically, the temperature for demoulding during pouring is 550-600°C, and the preheating temperature of the mold used for demoulding is 180-200°C.
[0021] The third technical solution of the present invention is the application of biodegradable Zn-Mg-Ca-Sr zinc alloy in degradable medical implants.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] A biodegradable Zn-Mg-Ca-Sr zinc alloy, wherein the mass fraction of magnesium is 1.10% to 1.20%, the total mass fraction of calcium and strontium is controlled to be 0.3%, and the Ca / Sr ratio (i.e., the mass fraction ratio of calcium to strontium, the same below) is 0, 0.5, 1, 1.5, and 2, respectively. The purpose is to study the influence of the change of calcium and strontium content on the microstructure and performance of the Zn alloy, so that Ca and Sr can simultaneously produce fine grain strengthening on the zinc matrix, determine the optimal Ca / Sr ratio, and improve the overall strengthening effect of the alloy; according to the Zn-Mg phase diagram, when the magnesium content is 2%, Mg2Zn will be produced in the hypoeutectic region. 11 According to the Zn-Ca phase diagram and the Zn-Sr phase diagram, adding a small amount of Ca and Sr (0.1wt.%~0.2wt.%) can form CaZn with good dispersion. 13 and SrZn 13 Strengthening phase. This preparation method shows that the addition of a small amount of strontium can ensure that SrZn is not generated. 13 Strengthening phase, partially dissolved in CaZn 13Phase improves the morphological roundness of the strengthening phase, and at the same time plays a role in the grain refinement of the strong component supercooling, which is an excellent zinc alloy grain refiner. In addition, the combined addition of Ca and Sr not only forms a certain strengthening phase, but also has a combined refinement and modification effect, completely avoiding the modification agent poisoning effect of a single excessive modification element (such as the modification failure and deterioration of excessive Sr, also known as the poisoning effect). Through the Ca / Sr ratio composite addition, the interaction between the two elements is used to maximize the synergistic grain refinement effect, and multiple toughening such as grain refinement and precipitation strengthening are achieved to synergistically improve the toughness of the bio-zinc alloy. The above-mentioned composition is determined based on experiments and phase diagrams. The advantage is that two grain boundary strengthening phases can be formed at the same time, and the strengthening phases are evenly distributed. The morphology of the strengthening phase is completely controllable according to the composite addition ratio. While ensuring the solid solution strengthening of the bio-zinc alloy, an effective strengthening phase and a certain number of strengthening phases can be generated, ensuring the overall strength, hardness and toughness of the alloy.
[0024] Furthermore, the matrix structure of the biodegradable Zn-Mg-Ca-Sr zinc alloy is metallic zinc dendrites, and the generated strengthening phases are Mg2Zn 11 、CaZn 13 and (Ca x , Sr. 1-x )Zn 13 Composite solid solution improves the strength and toughness of the alloy by refining the grains and strengthening the phase. In addition, there are few reports on the design and microstructure control technology of composite addition of Ca and Sr to zinc-magnesium alloy for strengthening and toughening.
[0025] Furthermore, the average grain size of pure zinc (η-Zn) in the cast state is 400-600 μm, while the average grain size of the matrix η-Zn of the Zn-Mg-Ca-Sr bio-zinc alloy is controllable in the range of 19.73-44.32 μm, which significantly refines the matrix grains. Grain refinement can improve the mechanical properties of the alloy and improve its resistance to corrosion by body fluids, thereby improving both toughness and corrosion resistance, which is more conducive to its application in clinical medical materials.
[0026] Furthermore, the Brinell hardness of pure zinc is 26.3 HBW, while the Brinell hardness of the Zn-Mg-Ca-Sr zinc alloy is 76.51-94.91 HBW, which significantly improves the hardness of the alloy.
[0027] A method for preparing a biodegradable Zn-Mg-Ca-Sr zinc alloy comprises the following steps: firstly preparing a zinc-magnesium alloy melt, weighing zinc and magnesium ingots, and thoroughly melting them in a silicon carbide crucible under the protection of an inert atmosphere, stirring and keeping the melt warm for a sufficient time; further preparing a Zn-Mg-Ca-Sr zinc alloy, weighing calcium and strontium particles, adding them to the zinc-magnesium alloy melt, keeping the melt warm and stirring the melt under the protection of an inert atmosphere, refining and slagging after sufficient reaction, and casting to obtain a Zn-Mg-Ca-Sr zinc alloy. By introducing calcium and strontium elements, the grain size of the matrix zinc can be significantly refined, achieving an excellent strong component supercooling refinement effect under the addition of composite elements, improving the organizational structure and performance of the biodegradable zinc alloy, and obtaining the best grain refinement and strengthening effect by adjusting the Ca / Sr ratio to obtain better strength, thus opening up new ideas for the application of zinc alloys in biodegradable materials. Through detection and characterization, comprehensive information such as the specific composition, morphology and structure of the alloy was obtained; the dense calcium and strontium zinc alloy obtained greatly improved the strength of the zinc alloy, and at the same time explained the influence of different Ca / Sr ratios on the microstructure and properties of the zinc alloy.
[0028] Furthermore, during the smelting process, high-purity argon gas is introduced and a covering agent is added for protection, which effectively reduces the oxidation of the raw materials and simultaneously performs a refining treatment on the melt, thereby improving the purity of the melt reaction.
[0029] Furthermore, according to the optimal parameters of the test process, the range of melt processing parameters is determined to ensure that magnesium, calcium and strontium in the melt can quickly and effectively diffuse and react to form a strengthening phase, and on the other hand, the reaction efficiency is improved and serious over-burning of low-melting point components is avoided. According to the Zn-Mg phase diagram, Zn-Ca phase diagram and Zn-Sr phase diagram, magnesium can be added to zinc to form Mg2Zn 11 Eutectic phase, the addition of calcium and strontium can form CaZn 13 Phase and SrZn 13 Phase is the main strengthening phase, and the strontium content is strictly controlled in order to neither produce a single SrZn 13 Phase, and can play the best strong component supercooling effect and grain refinement effect when added in combination with calcium. Therefore, the purpose of designing Zn-Mg-Ca-Sr zinc alloy in the present invention is to further improve the mechanical properties of zinc alloy by multi-phase composite strengthening and toughening means.
[0030] Furthermore, the Zn-Mg-Ca-Sr melt is allowed to stand in the furnace for 3 to 5 minutes before pouring to ensure the refinement effect and residue removal during the Sr metamorphism process, and to ensure that harmful inclusions and gases in the melt fully float and aggregate, which is beneficial to refining slag and purifying the melt.
[0031] Furthermore, a pouring temperature of 550 to 600°C can ensure that the melt fully reacts without being too hot to cause severe element burnout. The strengthening phase in the prepared alloy is fully generated and evenly distributed without structural defects. The preheating temperature of the mold used for demolding is 180 to 200°C, in order to ensure optimal demolding of the bio-zinc alloy and avoid surface oxidation.
[0032] In summary, the present invention strengthens and toughens the alloy by adding Ca and Sr in a composite ratio, thereby obtaining a biodegradable Zn-Mg-Ca-Sr zinc alloy with high strength, hardness and toughness, providing technical support for the application of zinc alloys in biodegradable materials.
[0033] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The microstructure diagram of the biodegradable Zn-Mg-Ca-Sr zinc alloy with a Ca / Sr ratio of 0;
[0035] Figure 2 The microstructure diagram of the biodegradable Zn-Mg-Ca-Sr zinc alloy with a Ca / Sr ratio of 0.5, where (a) is a low-magnification morphology and (b) is a high-magnification morphology;
[0036] Figure 3 The microstructure diagram of the biodegradable Zn-Mg-Ca-Sr zinc alloy with a Ca / Sr ratio of 1, where (a) is a low-magnification morphology and (b) is a high-magnification morphology;
[0037] Figure 4 The microstructure diagram of the biodegradable Zn-Mg-Ca-Sr zinc alloy with a Ca / Sr ratio of 1.5, including (a) low-magnification morphology and (b) high-magnification morphology;
[0038] Figure 5 Figure 2 shows the microstructure of the biodegradable Zn-Mg-Ca-Sr zinc alloy with a Ca / Sr ratio of 2, where (a) is a low-magnification morphology and (b) is a high-magnification morphology. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0041] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0042] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0043] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0044] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0045] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0046] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0047] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0048] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0049] The invention provides a biodegradable Zn-Mg-Ca-Sr zinc alloy and a preparation method and application thereof. Under the protection of high-purity argon, high-purity Ca and Sr particles are added to a zinc-magnesium melt, stirred at 550-600 DEG C for 20-30 minutes, and after sufficient reaction, the mixture is kept warm for 12-15 minutes, and poured into a preheated cylindrical graphite mold at 550-600 DEG C to obtain the Zn-Mg-Ca-Sr zinc alloy. Zn-Mg-Ca-Sr zinc alloys with different Ca / Sr ratios are provided, and guidance is provided for studying the influence of Ca and Sr elements on the structure and performance of the zinc alloy by observing the structure and microstructure of the zinc alloy and analyzing the strengthening effect.
[0050] The invention discloses a biodegradable Zn-Mg-Ca-Sr zinc alloy, which comprises 1.10% to 1.20% of Mg by weight, Ca and Sr accounting for less than or equal to 0.3% of the total mass percentage, the Ca / Sr ratio is respectively (0, 0.5, 1, 1.5, 2): 1, and the balance is Zn.
[0051] The matrix structure of biodegradable Zn-Mg-Ca-Sr zinc alloy is metallic zinc dendrites, and three strengthening phases are generated in the metallic zinc dendrites: eutectic rod-shaped Mg2Zn 11 Phase, irregular blocky CaZn 13 Phase and (Ca x , Sr. 1-x )Zn 13 Solid solution.
[0052] Eutectic rod-shaped Mg2Zn 11 The volume fractions of the phases are 9.36% (Ca / Sr=0), 24.33% (Ca / Sr=0.5), 26.24% (Ca / Sr=1), 23.56% (Ca / Sr=1.5), and 29.07% (Ca / Sr=2), respectively.
[0053] Irregular bulk CaZn distributed at grain boundaries 13 The volume fractions of the phases are 0% (Ca / Sr=0), 5.01% (Ca / Sr=0.5), 3.53% (Ca / Sr=1), 4.73% (Ca / Sr=1.5), and 2.89% (Ca / Sr=2), respectively. Sr is distributed in the CaZn phase in a solid solution state. 13 phase, which plays a role in strengthening component supercooling and refining grains.
[0054] The average grain sizes of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy are 44.32μm (Ca / Sr=0), 37.02μm (Ca / Sr=0.5), 36.11μm (Ca / Sr=1), 19.73μm (Ca / Sr=1.5), and 23.39μm (Ca / Sr=2).
[0055] The Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 76.51 HBW (Ca / Sr=0), 91.08 HBW (Ca / Sr=0.5), 84.95 HBW (Ca / Sr=1), 94.91 HBW (Ca / Sr=1.5), and 89.96 HBW (Ca / Sr=2).
[0056] The invention discloses a method for preparing a biodegradable Zn-Mg-Ca-Sr zinc alloy, which adopts high-purity raw materials and high-purity smelting technology for preparation, wherein the purity of the raw material Zn is greater than or equal to 99.995%, the purity of Mg is equal to 99.999%, the purity of Ca is equal to 99.9%, and the purity of Sr is equal to 99.99%; the method comprises the following steps:
[0057] S1. Preheat the silicon carbide crucible and raw materials to 180-200°C in a vacuum heat treatment furnace for drying. Considering the burning loss of the raw materials, weigh the materials with an electronic balance according to the weight ratio;
[0058] Alloy density ρ 合金 for:
[0059] ρ 合金 =M / V
[0060] Among them, the alloy density ρ 合金 The unit is g / cm 3 , M is the alloy mass, and V is the alloy volume.
[0061] S2. High-purity argon is introduced into a well-sealed resistance furnace. After the surfaces of zinc ingots and magnesium ingots are cleaned and dried, they are placed one by one into the bottom of the silicon carbide crucible using crucible tongs. The ingots are kept at 550-600°C for 20-30 minutes to completely melt them.
[0062] The melting point of pure zinc is 419.53°C. The melting temperature is controlled at 550-600°C and the insulation time is 20-30 minutes to make the zinc melt completely.
[0063] High-purity calcium and strontium particles are slowly added to the molten zinc-magnesium melt, and a stirring device is used at the same time. The stirring speed is 50-80 rpm, and the mixture is stirred at 550-600° C. for 20-30 minutes to allow calcium and strontium to fully react. The mixture is then kept warm in the furnace for 12-15 minutes to obtain a Zn-Mg-Ca-Sr zinc alloy melt, in which the total mass fraction of calcium and strontium is 0.3%, and the Ca / Sr ratios are 0, 0.5, 1, 1.5, and 2, respectively.
[0064] The S3 and Zn-Mg-Ca-Sr zinc alloy melts are allowed to stand in the furnace for 3 to 5 minutes to ensure that harmful inclusions in the melt are fully floated and gathered, and the slag is refined and removed. The pouring temperature is obtained using a temperature sensor, and the melt is poured into a preheated cylindrical graphite mold at 550 to 600°C. The Zn-Mg-Ca-Sr zinc alloy ingot is demolded, and the preheating temperature of the mold used for demolding is 180 to 200°C.
[0065] The biodegradable Zn-Mg-Ca-Sr zinc alloy prepared with different Ca / Sr ratios and composite addition modification treatment was subjected to microstructure observation, structural characterization and hardness test characterization.
[0066] The specific morphology of the zinc alloy was observed by optical electron microscopy, field emission scanning electron microscopy (model GeminiSEM 500) and X-ray diffraction (the 2θ range of XRD was 10-90, the current was 200 mA, the voltage was 40 KV, and the scanning rate was 2° / min). The hardness of the alloy was tested using a Brinell hardness tester and a microhardness tester.
[0067] The biodegradable Zn-Mg-Ca-Sr zinc alloy of the present invention can be applied to degradable medical implants, including bone nails, bone plates, cardiovascular stents, anastomosis devices and sutures.
[0068] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0069] Example 1
[0070] A preparation process of Zn-Mg-Ca-Sr zinc alloy subjected to composite addition modification treatment with different Ca / Sr ratios specifically comprises the following steps:
[0071] S1. Cut high-purity zinc and magnesium ingots into small pieces with a sawing machine, grind them with a grinder, clean them with alcohol and acetone ultrasonically, and dry them in a vacuum heat treatment furnace at 180°C to remove the oxide film on the surface of the material and the oil stain on the sawing machine;
[0072] S2. Prepare Zn-1.1wt.%Mg zinc alloy, and prepare the ingredients by weight percentage, Mg: 1.10%, and the balance is Zn; heat the well-sealed pit-type resistance furnace to 600℃, introduce high-purity argon gas, add high-purity zinc and magnesium into the crucible piece by piece, keep warm for 40 minutes to completely melt, add high-purity calcium and strontium particles, and after melting, turn on the stirring device at a speed of 50 rpm, stir at 600℃ for 20 minutes, keep warm in the furnace for 12 minutes after sufficient reaction, and obtain Zn-1.2wt.%Mg zinc alloy melt;
[0073] S3. The alloy melt is allowed to stand in the furnace and refined and slag removed, and then poured into a preheated mold at 550° C. and demolded to obtain a Zn-1.1 wt. % Mg zinc alloy ingot.
[0074] In Example 1, a Zn-1.1wt.%Mg bio-zinc alloy was prepared by adding high-purity calcium and strontium particles to the zinc-magnesium melt. The analysis and confirmation of the microstructure of the alloy found that after adding 1.1wt.%Mg, Mg2Zn 11 Strengthening phase. The formation of strengthening phase can significantly improve the hardness of the alloy.
[0075] Example 2
[0076] A preparation process of Zn-Mg-Ca-Sr zinc alloy subjected to composite addition modification treatment with different Ca / Sr ratios specifically comprises the following steps:
[0077] S1. Cut high-purity zinc and magnesium ingots into small pieces with a sawing machine, grind them with a grinder, clean them with alcohol and acetone ultrasonically, and dry them in a vacuum heat treatment furnace at 180°C to remove the oxide film on the surface of the material and the oil stain on the sawing machine;
[0078] S2. Prepare Zn-1.2wt.%Mg-0.1wt.%Ca-0.2wt.%Sr zinc alloy, and prepare the ingredients by weight percentage, Mg: 1.2%, Ca: 0.1%, Sr: 0.2%, and the balance is Zn; heat the well-sealed pit-type resistance furnace to 600℃, introduce high-purity argon gas, add high-purity zinc and magnesium into the crucible piece by piece, keep warm for 40 minutes to make them completely melted, add high-purity calcium and strontium particles, and after melting, turn on the stirring device at a speed of 50 rpm, stir at 600℃ for 20 minutes, make it fully reacted, and keep warm in the furnace for 12 minutes to obtain Zn-1.2wt.%Mg-0.1wt.%Ca-0.2wt.%Sr zinc alloy melt;
[0079] S3. The alloy melt is allowed to stand in the furnace and refined and deslagging is performed, and then poured into a preheated mold at 550° C. and demolded to obtain a Zn-1.2wt.%Mg-0.1wt.%Ca-0.2wt.%Sr zinc alloy ingot.
[0080] In Example 2, high-purity calcium and strontium particles were added to the zinc-magnesium melt to prepare a Zn-1.2wt.%Mg-0.1wt.%Ca-0.2wt.%Sr bio-zinc alloy. The analysis and confirmation of the microstructure of the alloy found that after adding 0.1wt.%Ca and 0.2wt.%Sr, CaZn precipitated in the structure. 13 and (Ca x ,Sr 1-x )Zn 13 Solid solution. The formation of two strengthening phases can significantly improve the hardness of the alloy, and the addition of Ca and Sr is beneficial to the refinement of the metal zinc matrix.
[0081] Example 3
[0082] A preparation process of Zn-Mg-Ca-Sr zinc alloy subjected to composite addition modification treatment with different Ca / Sr ratios specifically comprises the following steps:
[0083] S1. Cut high-purity zinc and magnesium ingots into small pieces with a sawing machine, grind them with a grinder, clean them with alcohol and acetone ultrasonically, and dry them in a vacuum heat treatment furnace at 180°C to remove the oxide film on the surface of the material and the oil stain on the sawing machine;
[0084] S2. Prepare Zn-1.2wt.%Mg-0.15wt.%Ca-0.15wt.%Sr zinc alloy, and prepare the ingredients by weight percentage, Mg: 1.2%, Ca: 0.15%, Sr: 0.15%, and the balance is Zn; heat the well-sealed pit-type resistance furnace to 600℃, introduce high-purity argon gas, add high-purity zinc and magnesium into the crucible piece by piece, keep warm for 40 minutes to make them completely melted, add high-purity calcium and strontium particles, and after melting, turn on the stirring device at a speed of 50 rpm, stir at 600℃ for 20 minutes, and keep warm in the furnace for 12 minutes after sufficient reaction to obtain Zn-1.2wt.%Mg-0.15wt.%Ca-0.15wt.%Sr zinc alloy melt;
[0085] S3. The alloy melt is allowed to stand in the furnace and refined and deslagging is performed, and then poured into a preheated mold at 550° C. and demolded to obtain a Zn-1.2wt.%Mg-0.15wt.%Ca-0.15wt.%Sr zinc alloy ingot.
[0086] Example 4
[0087] A preparation process of Zn-Mg-Ca-Sr zinc alloy subjected to composite addition modification treatment with different Ca / Sr ratios specifically comprises the following steps:
[0088] S1. Cut high-purity zinc and magnesium ingots into small pieces with a sawing machine, grind them with a grinder, clean them with alcohol and acetone ultrasonically, and dry them in a vacuum heat treatment furnace at 180°C to remove the oxide film on the surface of the material and the oil stain on the sawing machine;
[0089] S2. Prepare Zn-1.2wt.%Mg-0.18wt.%Ca-0.12wt.%Sr zinc alloy, and prepare the ingredients by weight percentage, Mg: 1.2%, Ca: 0.18%, Sr: 0.12%, and the balance is Zn; heat the well-sealed pit-type resistance furnace to 600℃, introduce high-purity argon gas, add high-purity zinc and magnesium into the crucible piece by piece, keep warm for 40 minutes to make them completely melted, add high-purity calcium and strontium particles, and after melting, turn on the stirring device at a speed of 50 rpm, stir at 600℃ for 20 minutes, and keep warm in the furnace for 12 minutes after sufficient reaction to obtain Zn-1.2wt.%Mg-0.18wt.%Ca-0.12wt.%Sr zinc alloy melt;
[0090] S3. The alloy melt is allowed to stand in the furnace and refined and deslagging is performed, and then poured into a preheated mold at 550° C. and demolded to obtain a Zn-1.2wt.%Mg-0.18wt.%Ca-0.12wt.%Sr zinc alloy ingot.
[0091] Example 5
[0092] A preparation process of Zn-Mg-Ca-Sr zinc alloy subjected to composite addition modification treatment with different Ca / Sr ratios specifically comprises the following steps:
[0093] S1. Cut high-purity zinc and magnesium ingots into small pieces with a sawing machine, grind them with a grinder, clean them with alcohol and acetone ultrasonically, and dry them in a vacuum heat treatment furnace at 180°C to remove the oxide film on the surface of the material and the oil stain on the sawing machine;
[0094] S2. Prepare Zn-1.2wt.%Mg-0.2wt.%Ca-0.1wt.%Sr zinc alloy, and prepare the ingredients by weight percentage, Mg: 1.2%, Ca: 0.2%, Sr: 0.1%, and the balance is Zn; heat the well-sealed pit-type resistance furnace to 600℃, introduce high-purity argon gas, add high-purity zinc and magnesium into the crucible piece by piece, keep warm for 40 minutes to make them completely melted, add high-purity calcium and strontium particles, and after melting, turn on the stirring device at a speed of 50 rpm, stir at 600℃ for 20 minutes, and keep warm in the furnace for 12 minutes after sufficient reaction to obtain Zn-1.2wt.%Mg-0.2wt.%Ca-0.1wt.%Sr zinc alloy melt;
[0095] S3. The alloy melt is allowed to stand in the furnace and refined and slag removed, and then poured into a preheated mold at 550° C. and demolded to obtain a Zn-1.2wt.%Mg-0.2wt.%Ca-0.1wt.%Sr zinc alloy ingot.
[0096] See also Figures 1 to 5 , respectively, are the metallographic microstructures of Zn-1.2wt.%Mg, Zn-1.2wt.%Mg-0.1wt.%Ca-0.2wt.%Sr, Zn-1.2wt.%Mg-0.15wt.%Ca-0.15wt.%Sr, Zn-1.2wt.%Mg-0.18wt.%Ca-0.12wt.%Sr and Zn-1.2wt.%Mg-0.2wt.%Ca-0.1wt.%Sr zinc alloys. It can be seen that the organization consists of Zn matrix, α-Zn+Mg2Zn 11 Eutectic structure, irregular square CaZn 13 Phase and a small amount (Ca x , Sr. 1-x )Zn 13 Solid solution composition.
[0097] In summary, the present invention provides a biodegradable Zn-Mg-Ca-Sr zinc alloy and a preparation method and application thereof. Under the protection of high-purity argon and a covering agent, by compositely adding Ca and Sr elements, a biodegradable Zn-Mg-Ca-Sr zinc alloy with calcium-strontium composite addition and modification treatment, which has rarely been studied, is obtained. From the microstructure and Brinell hardness measurement of the biodegradable Zn-Mg-Ca-Sr zinc alloy, it can be found that the mechanical properties of the alloy are improved by compositely adding Ca and Sr for strengthening.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A biodegradable Zn-Mg-Ca-Sr zinc alloy, characterized in that: The elements contained are calculated by weight percentage: Mg 1.10% to 1.20%, the total amount of Ca and Sr is equal to 0.3%, the balance is Zn, the mass percentage ratio of Ca to Sr is 0, 0.5, 1, 1.5 or 2, the matrix structure of the biodegradable Zn-Mg-Ca-Sr zinc alloy is η-Zn dendrites, and the strengthening phases are eutectic rod-shaped Mg2Zn distributed between the dendrites. 11 Phase, intragranular and grain boundary bulk CaZn 13 Phase and (Ca x , Sr. 1-x )Zn 13 Solid solution; When the mass percentage ratio of Ca to Sr is 0, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 9.36%; when the mass percentage ratio of Ca to Sr is 0.5, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 24.33%, CaZn 13 The volume fraction of the phase is 5.01%; when the mass percentage ratio of Ca and Sr is 1, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 26.24%, CaZn 13 The volume fraction of the phase is 3.53%; when the mass percentage ratio of Ca to Sr is 1.5, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 23.56%, CaZn 13 The volume fraction of the phase is 4.73%; when the mass percentage ratio of Ca to Sr is 2, the eutectic rod-shaped Mg2Zn 11 The volume fraction of the phase is 29.07%, irregular blocky CaZn 13 The volume fraction of the phase is 2.89%; When the mass percentage ratio of Ca to Sr is 0, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 44.32μm; when the mass percentage ratio of Ca to Sr is 0.5, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 37.02μm; when the mass percentage ratio of Ca to Sr is 1, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 36.11μm; when the mass percentage ratio of Ca to Sr is 1.5, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 19.73μm; when the mass percentage ratio of Ca to Sr is 2, the average grain size of the matrix of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 23.39μm; When the mass percentage ratio of Ca and Sr is 0, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 76.51 HBW; when the mass percentage ratio of Ca and Sr is 0.5, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 91.08 HBW; when the mass percentage ratio of Ca and Sr is 1, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 84.95 HBW; when the mass percentage ratio of Ca and Sr is 1.5, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 94.91 HBW; when the mass percentage ratio of Ca and Sr is 2, the Brinell hardness of the biodegradable Zn-Mg-Ca-Sr zinc alloy is 89.96 HBW.
2. A method for preparing the biodegradable Zn-Mg-Ca-Sr zinc alloy as claimed in claim 1, characterized in that: The following steps are involved: In an inert atmosphere, zinc and magnesium are heated in sequence until they are completely melted to obtain a melt, and then calcium and / or strontium particles are added to the melt, the temperature is increased and the melt is fully stirred, and the melt is kept warm to obtain a Zn-Mg-Ca-Sr zinc alloy melt; The Zn-Mg-Ca-Sr zinc alloy melt is allowed to stand, refined and slag removed, and then poured and demolded to obtain the biodegradable Zn-Mg-Ca-Sr zinc alloy.
3. The method for preparing the biodegradable Zn-Mg-Ca-Sr zinc alloy according to claim 2, characterized in that: The zinc and magnesium are heated until they are completely melted to obtain a melt as follows: The flow rate of the inert gas is controlled to be 15-20 L / min, and the melting temperature is controlled to be 550-600° C. to heat zinc and magnesium, and the temperature is kept for 30-40 minutes to obtain a zinc-magnesium melt.
4. The method for preparing the biodegradable Zn-Mg-Ca-Sr zinc alloy according to claim 2, characterized in that: The preparation of Zn-Mg-Ca-Sr zinc alloy melt is specifically as follows: The stirring speed is controlled to be 50-80 rpm, the mixture is stirred at 550-600° C. for 20-30 minutes, and then kept warm for 12-15 minutes to obtain a Zn-Mg-Ca-Sr zinc alloy melt.
5. The method for preparing the biodegradable Zn-Mg-Ca-Sr zinc alloy according to claim 2, characterized in that: The standing time is 3 to 5 minutes.
6. The method for preparing the biodegradable Zn-Mg-Ca-Sr zinc alloy according to claim 2, characterized in that: The temperature for demoulding during pouring is 550-600°C, and the preheating temperature of the mold used for demoulding is 180-200°C.
7. Use of the biodegradable Zn-Mg-Ca-Sr zinc alloy according to claim 1 in degradable medical implant devices.
Citation Information
Patent Citations
Biomedical degradable alloy as well as preparation method and application thereof
CN115161513A